The Role of HIV Research in Building Health System Capacity in Developing Countries - Zewdie, D.; Cahn, P.; McClure, C.; Bataringaya, J. (2012)
PURPOSE OF REVIEW: There is growing recognition that greater investment in research is needed to expand our knowledge and understanding of how to scale up HIV programmes effectively and equitably in the context of weak health systems. Current debates acknowledge that there remains a gap in evidence on how HIV resources can best be managed to contribute to building health system capacity; how to integrate HIV interventions into primary healthcare systems; and how HIV scale-up is affecting other disease programmes. RECENT FINDINGS: Findings suggest that global health initiatives, including HIV/AIDS programmes, should allocate a set portion of funding for research and knowledge generation in improving health system performance. Forms of HIV research with potential for building health system capacity in developing countries include clinical research, implementation and operations research, quality improvement research, economic evaluation and cost-effectiveness, HIV surveillance and population-based surveys, and monitoring and evaluation. SUMMARY: In this review, we present an overview of the imperative for HIV research in building health system capacity, provide examples of current trends and the forms of research with potential for enhancing health system performance, and highlight priorities for enhancing the role of HIV research in building health system capacity.